Manejo agronómico del cultivo de cebolla (allium cepa. l) var. camaneja en truz bajo - Chepén, La Libertad - Mendoza Cerna, Anni Lizeth (2016)
The aim of this study was to describe the agronomic onion crop management through surveys in TruzBajo, province of Chepén, La Libertad department. For the development this the onion growers were surveyed , the results show the agronomic management of the crop of onion variety Camaneja,the farmers do not use certified seed prepare their seedbeds , the transplant was carried out with seedlings of 35-40 days old , disinfect the seed before transplanting with Homai using 4 grams per kilo of seed,planting conducted mostly in beds , the system of drip irrigation , the planting distance varies 0.6 - 1 m between rows by 0.10 to 0.20 m between plants , chemical fertilizer use. The most important pest of the crop in the area is Trips tabaci (trips) and diseases of importance as Stemphylium vesicarium (dry point) Botrytis squamosa (white or gray mold) using as control measure applying insecticides and preventive and curative fungicides. Harvest is done manually at 80 days after transplantation and when it reaches physiological maturity complete. After this onion bulbs are left in the field for 6 days (curing) to dry and subsequently selected by size is placed in bags (mesh) 110 kilos for marketing.